2019
DOI: 10.5946/ce.2018.154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes between Plastic Stent and Novel Lumen-apposing Metal Stent for Endoscopic Ultrasound-Guided Drainage of Peripancreatic Fluid Collections

Abstract: Background/Aims Endoscopic ultrasound (EUS)-guided transmural drainage for peripancreatic fluid collections (PFCs) has gained wide acceptance as a nonsurgical intervention. Although a lumen-apposing metal stent (LAMS) was recently introduced, there are few data comparing the clinical outcomes between LAMS and plastic stent (PS) drainage. Methods Endoscopy databases of all patients who had undergone EUS-guided drainage for PFCs were searched and the clinical outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Our literature searches led to the identification of 1400 articles. After screening the titles and abstracts, 20 studies were found to meet our eligibility criteria ( Figure 1) [3,9,10,[12][13][14][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. A total of 1534 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature searches led to the identification of 1400 articles. After screening the titles and abstracts, 20 studies were found to meet our eligibility criteria ( Figure 1) [3,9,10,[12][13][14][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. A total of 1534 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the matched cautery-enhanced delivery systems decrease technical difficulty and shorten the procedural time. Even though some studies show LAMS might have a slight advantage over plastic stents in terms of clinical success[ 27 , 59 , 60 ], more studies have shown that there were no differences between LAMS and plastic stents regarding the technical success rate, clinical success, recurrence in drainage of pancreatic, and peripancreatic collections[ 24 , 25 , 60 - 62 ]. In contrast, the bleeding risk (including pseudoaneurysm bleeding, which is life-threatening and may require immediate interventional radiology-guided coil embolization or open surgery) is higher in the LAMS group[ 32 , 61 , 62 ].…”
Section: Walled Off Necrosismentioning
confidence: 99%
“…В некоторых многопрофильных ЛПУ совмещают использование обычной методики ТМД с УЗИ, которое называется дренированием при помощи ЭУС, с целью определения местоположения кисты и расстояния от нее до стенки кишечника [59]. Большинство исследователей пришли к выводу, что дренирование при помощи ЭУС имеет лучшие результаты в сравнении с традиционной методикой ТМД, обеспечивая более точную визуализацию псевдокисты и окружающей анатомии, что помогает оператору выбрать оптимальные места для проколов и избежать повреждения крупных сосудов [60,61]. Эти данные делают интра-и послеоперационные осложнения при дренировании с помощью ЭУС менее серьезными по сравнению с осложнениями после традиционного ТМД.…”
Section: эндоскопическое дренированиеunclassified